DEVELOPMENT OF CUSTOMER RELATIONSHIP MANAGEMENT APPLICATION USING DYNAMIC CRM FRAMEWORK - ANNA DARA ANDRIANA (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2022)
In the development of technology, currently it has covered all fields, including in the business field. Customer Relationship Management (CRM) is approach used by companies in fostering good relationships with customers. Managing relationships with customers has been proven to increase the company's income and can meet customer satisfaction, so that customers become loyal customers. The purpose of this CRM application is to attract as many new customers as possible, as well as retain old customers and increase customer loyalty. In CRM, companies and customers will benefit. The company will get profits as well as increasing income, and customers will get satisfaction for the services provided by the company. To create a CRM, the Dynamic CRM Framework is used which can simplify the development and analysis and design of CRM applications. Currently, CRM is a very important segment in customer management. So, companies can easily build good relationships with each of their customers by recognizing every customer in the company. This application is very helpful in managing good relations between companies and customers